Strategies to Minimize Negative Effects of AI Applications for Independent English Learning Situation - Norhayati, Norhayati; Sulistyowati, Sulistyowati; Jayanti, Sherly (Juwara: Jurnal Wawasan dan Aksara, 2025)
Applications based on artificial intelligence are becoming widely used in education as well. These applications are utilized by both students and professors. Artificial intelligence-based applications that are available for free and indefinite use raise worries about the possibility of abuse. This study aimed to minimize the negative impacts of using artificial intelligence (AI)-based applications on independent English learning activities. The research method used was a descriptive qualitative approach, with data collection techniques through semi-structured interviews with 15 lecturers and open questionnaires with 169 students from four educational institutions in Palangkaraya City. The results of the study showed that 93% of students and 87% of lecturers stated that the use of AI applications has the potential to trigger violations of academic ethics, especially plagiarism and copyright infringement, if users are not prepared with critical awareness. The key findings of this study underlined the importance of strengthening ethical-based digital literacy through three main efforts, they are1) socialization of guidelines for the use of AI in accordance with academic principles, 2) integration of technology ethics modules in the learning curriculum, and 3) development of a collaborative-based supervision system between institutions, lecturers, and students.